Expanding horizons: The impact of international mobility programs on faculty development and student learning - Eidson, Jacquelyn Irene (Journal of International Students, 2025)
International mobility programs provide transformative opportunities for faculty, enriching their pedagogical practices and ultimately benefiting students. Thematic analysis was used to identify patterns in faculty narratives related to professional development, pedagogical change, and student impact. Through a combination of qualitative interviews with American and European faculty and personal reflections from Fulbright and other international collaborations, this study explores how global experiences shape teaching, learning, and cross-cultural engagement. Against the backdrop of recent funding freezes and policy shifts that threaten international exchanges, this article argues that global academic mobility remains vital to fostering innovation, resilience, and inclusivity within higher education. Recommendations for sustaining and strengthening international collaboration are offered to promote interconnected academic environments in an increasingly uncertain global landscape.